LEGAL EDUCATION FAILURES, SPONTANEOUS BYPASSES, AND THE REPRODUCTION OF HIERARCHY IN BRAZIL: some preliminary thoughts - Trubek, David; Alves, Camila (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2020)
In Prado and Trebilcock’s book, Institutional Bypasses: A Strategy to Promote Reforms for Development, the authors identify what they call a spontaneous bypass. These are alternatives that emerge as decentralized individuals and groups look for substitutes for a system that is not working as it could or should. Although these spontaneous bypasses - often called “workarounds” - are created as uncoordinated solutions, collectively they offer alternative pathways to dysfunctional institutions. By looking at ways people have sought to work around such roadblocks to development, the authors suggest, we can better understand the dynamics of a dysfunctional system and find ideas that might be used for reform. In Brazil we might see training in law schools for advanced corporate law practice as a suboptimal system surrounded by several bypasses or “workarounds”. In this paper, we identify this as another potential case study, in addition to the ones discussed in the book, analyze its (perverse) implications and outline a possible research project on this topic.